Integrating Rhizoma Perennial Peanut into Bahiagrass Pastures Enhances Beneficial Soil Microbes in Florida - Hui-Ling Liao; Adesuwa Erhunmwunse (EDIS)
Soil microorganisms, including soil bacteria and fungi, play important roles in pasture systems. They contribute to enhanced soil structure, nutrient cycling, and plant resilience. This publication discusses effects of bahiagrass and rhizoma perennial peanut integration on soil microbial diversity. Written by Hui-Ling Liao and Adesuwa S. Erhunmwunse, and published by the UF/IFAS Department of Agronomy, July 2024.